ENGARUH RANGE OF MOTION (ROM) PASIF TERHADAP KEKUATAN OTOT PADA PASIEN STROKE DENGAN PENURUNAN KESADARAN DI RUANG HCU IGD RSUD Dr. MOEWARDI DI SURAKARTA TAHUN 2012 - Sri Mulyanti (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstractIntroduction: Each year, approximately 15 million people worldwide have a stroke. In Indonesia based on the census of population and demography Indonesia (SKDI) in 2010 as many as 3.6 million per year with a prevalence of 8.3 per 1,000 population. Stroke is a neurological disease that appeared suddenly in a short time. One of the clinical manifestations of the most common is hemiparese. Complications hemiparese in muscles and joints is muscle atrophy and joint contractures. One treatment technique to prevent these complications is the Range Of Motion (ROM) passive exercise.Objective: (1) Identify the characteristics of stroke patients with loss of consciousness (2) Identify the muscle power stroke patients with loss of consciousness (3) to analyze the influence Range Of Motion (ROM) of the passive muscle strength in stroke patients with loss of consciousness. Method: This research is quasy experiment with design one-group pretestposttest design. The population in this study were 13 stroke patients with critical conditions in Space High Care Unit Hospital Dr Moewardi in Surakarta. Samples were taken by sampling saturated. Data were analyzed with the Wilcoxon or Z test using SPSS for windows 16 series.Result: (1) The muscle strength before passive ROM was 11 people (68.8%) is trace, 5 people (31.2%) is poor, and of zero muscle strength, fair, good, and normally does not exist. (2) Muscle strength stroke after passive ROM is 7 (43.8%) of respondents with poor muscle strength scale, 9 people (56.2%) fair, and scale of zero muscle strength, trace, good, and normally there is not exist(0%). (3) The results of the statistical Wilcoxon or Z test significance value (p) of 0000 which means that there are differences in muscle strength scale before and after passive Range Of Motion. (ROM) patients with loss of consciousness. Conclusion: Range Of Motion (ROM) is effective for improving muscle strength for stroke patients with loss of consciousness in H ospital Dr Moewardi Surakarta Keywords: Stroke, Hemiparese, Range Of Motion